The School Principal's Visionary Leadership in Improving Student Achievement (Case Study at Shalahudin Junior High School Malang) - Chasanah, Usfatul; Nurabadi, Ahmad; Zulkarnain, Wildan; Timan, Agus (Journal of Education for Sustainability and Diversity, 2025)
Principals in the field of education can determine the goals to be achieved in the future, such as improving student achievement. This study aims to describe the formulation and implementation of vision, the principal's visionary leadership style, the principal's strategy in improving achievement, and the character developed by the principal. The method in this research uses a qualitative approach of case study design with data collection techniques of interview, observation, and documentation. The results of this research show (1) The formulation and implementation of the vision at Shalahudin Junior High School is carried out by deliberation by gathering all stake holders; (2) the leadership style of the principal of Shalahudin Junior High School Malang is a visionary leadership style; (3) the principal's strategy in improving student achievement is by having activities based on religious aspects, developing talents and interests, making TTS programs; and (3) the characters developed by the principal are discipline, responsibility, Islamic, orderly, achievers, and entrepreneurs.